High-grade endometrial cancer presents with malignancy-associated disseminated intravascular coagulation: A case report - Jennifer Hansen; Andreea Dinicu; Johanna Kelley; Lindsey Beffa (Gynecologic Oncology Reports)
Malignancy-associated DIC is uncommon and when it does occur, is often associated with hematologic malignancies rather than solid tumors. In this case, we describe an unusual case when a patient with advanced stage high-grade endometrial adenocarcinoma presented to care with vision loss and deep vein thrombosis, found to be in disseminated intravascular coagulation (DIC). The patient suffered many complications from her DIC, which was briefly managed with systemic therapy for her underlying malignancy but ultimately led to her death. DIC has been reported in the literature rarely for gynecologic malignancies, and never as presenting symptom for high-grade endometrial adenocarcinoma.